Shakespeare, the Queen's Men, and the Elizabethan performance of history - Walsh, Brian (Professor of English) (Cambridge, UK ; New York : Cambridge University Press, 2009)
"The Elizabethan history play was one of the most prevalent dramatic genres of the 1590s, and so was a major contribution to Elizabethan historical culture. The genre has been well served by critical studies that emphasize politics and ideology; however, there has been less interest in the way history is interrogated as an idea in these plays. Drawing in period-sensitive ways on the field of contemporary performance theory, Walsh looks at the Shakespearean history play from a fresh angle, by first analyzing the foundational work of the Queen's Men, the playing company that invented the popular history play. Through innovative readings of their plays including The Famous Victories of Henry V before moving on to Shakespeare's 1 Henry VI, Richard III, and Henry V, this book investigates how the Queen's Men's self-consciousness about performance helped to shape Shakespeare's dramatic and historical imagination"--Provided by publisher.
"Longing on a large scale is what makes history." Don DeLillo, Underworld In his 1589 treatise The Arte of English Poesie, George Puttenham diagnosed the limited ability of humans to perceive history. The past, according to Puttenham, is that which "we are not able ... to attaine to the knowledge of, by any of our ences." History is defined by its inalienable absence. It exists only in forms of textual or pictorial representation, such as prose works, poetry, and illustrations, or in embodied acts such as storytelling and theatrical playing. In sixteenth-century England, these forms flourished as varying responses to a heightened awareness of the absence of history, an awareness that the intellectual ambitions of the Renaissance precipitated. Of all the forms of history, performance alone supplies a pretense of sensual contact with the vanished past through the bodies that move and speak on stage. The history plays that I consider in this book, from the repertory of the Queen's Men and by Shakespeare, grew out of a vibrant Elizabethan historical culture, and they in turn helped to shape a new historical outlook"--Provided by publisher.
Introduction; 1. Dialogues with the dead: history, performance, and Elizabethan theater; 2. Theatrical time and historical time: the temporality of the past in The Famous Victories of Henry V; 3. Figuring history: truth, poetry, and report in The True Tragedy of Richard III; 4. 'Unkind division': the double absence of performing history in 1 Henry VI; 5. Richard III and Theatrum Historiae; 6. Henry V and the extra-theatrical historical imagination; Conclusion: traces of Henry/traces of history.
Includes bibliographical references and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Shakespeare, William, -- 1564-1616 -- Knowledge -- History; Queen's Men (Theater company) -- History; Shakespeare, William, -- 1564-1616; Queen's Men (Theater company); Queen's Men; Shakespeare, William; Historical drama, English -- History and criticism; Literature and history -- Great Britain; English drama -- Early modern and Elizabethan, 1500-1600 -- History and criticism; Theater -- England -- History -- 16th century; Théâtre historique anglais -- Histoire et critique; Littérature et histoire -- Grande-Bretagne.; Théâtre anglais -- 16e siècle -- Histoire et critique; Théâtre -- Angleterre -- Histoire -- 16e siècle.; DRAMA -- English, Irish, Scottish, Welsh; History; English drama -- Early modern and Elizabethan; Historical drama, English; Literature and history; Theater; England; Great Britain; Historisches Drama; 1500-1600; Electronic books; Criticism, interpretation, etc; History